Seawater exposure causes hydraulic damage in dying Sitka-spruce trees. Issue 2 (22nd June 2021) - Zhang, Hongxia; Li, Xinrong; Wang, Wenzhi; Pivovaroff, Alexandria L.; Li, Weibin; Zhang, Peipei; Ward, Nicholas D.; Myers-Pigg, Allison; Adams, Henry D.; Leff, Riley; Wang, Anzhi; Yuan, Fenghui; et al.
Abstract: Sea-level rise is one of the most critical challenges facing coastal ecosystems under climate change. Observations of elevated tree mortality in global coastal forests are increasing, but important knowledge gaps persist concerning the mechanism of salinity stress-induced nonhalophytic tree mortality. We monitored progressive mortality and associated gas exchange and hydraulic shifts in Sitka-spruce ( Picea sitchensis ) trees located within a salinity gradient under an ecosystem-scale change of seawater exposure in Washington State, USA. Percentage of live foliated crown (PLFC) decreased and tree mortality increased with increasing soil salinity during the study period. A strong reduction in gas exchange and xylem hydraulic conductivity ( K s ) occurred during tree death, with an increase in the percentage loss of conductivity (PLC) and turgor loss point (πtlp ). Hydraulic and osmotic shifts reflected that hydraulic function declined from seawater exposure, and dying trees were unable to support osmotic adjustment. Constrained gas exchange was strongly related to hydraulic damage at both stem and leaf levels. Significant correlations between foliar sodium (Na + ) concentration and gas exchange and key hydraulic parameters ( K s, PLC, and πtlp ) suggest that cellular injury related to the toxic effects of ion accumulation impacted the physiology of these dying trees. This study provides evidence of toxic effects on the cellular function that manifests in all aspects of plant functioning, leading to unfavourable osmotic and hydraulic conditions. Abstract : Hydraulic and osmotic shifts during tree death under seawater exposure are related to the toxic effects of ion accumulation on the maintenance of cellular function.